Accessing and Implementing Human Rights and Justice - Mills, Kurt; Labonte, Melissa; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Accessing human rights and justice mechanisms is a pressing issue in global politics. Although an understanding of justice is inherent in broad human rights discourses, there is no clear consensus on how to develop adequate means of accessing them in order to make a difference to people s lives. Further, expansions of the boundaries of both human rights and justice make any clear and settled understanding of the relation difficult to ascertain. This volume tackles these issues by focusing on the dilemmas of accessing and implementing human rights and justice across a range of empirical contexts while also investigating a range of conceptual approaches to, and understandings of, justice, including issues of equality, retribution, and restoration, as well as justice as a transnational professional project. The contributors, representing a range of disciplinary backgrounds and diverse voices, offer empirical examples from Afghanistan, Democratic Republic of the Congo, Syria, Tunisia, and Uganda to explore the issues of accessing and implementing human rights and justice in conflict, post-conflict, and transitional settings. This work will be of interest to students and scholars of international relations, human rights, international criminal justice, and conflict response.
Introduction -- Kurt Mills and Melissa Labonte -- 1. Justice and (global) constitutionalism: the International Criminal Court in the global order -- Anthony F. Lang, Jr. and Andrea Birdsall -- 2. Syria and the responsibility to prosecute: norm promotion in the UN Security Council -- Carrie Booth Walling -- 3. International criminal justice as political strategy: asymmetry of opportunity? -- Yuna Christine Han -- 4. Human rights, justice and peace in Uganda: bridging the global and the local -- Kurt Mills -- 5. Redressing unlawful use of force in armed conflict: the role of international human rights law -- Vito Todeschini -- 6. "Droits de lhomme, bien sr!" human rights and transitional justice in Tunisia -- Mariam Salehi.
Includes bibliographical references and index.
Also available in print format.
Keywords: POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy; Global Institutions; Humanitarianism; Human Rights; Human Right Justice; Labonte; Responsibility to Protect; Weiss; Criminal justice, Administration of; Human rights; Electronic books